Implementasi Manajemen Administrasi Pendidikan Dalam Mendukung Program Adiwiyata Di MI Al Ishlah Bobos Cirebon - Luthfanie, Dhika; Inayah, Dewi; Suklani, Suklani (JURNAL MANAJEMEN PENDIDIKAN, 2026)
IMPLEMENTATION OF EDUCATIONAL ADMINISTRATION MANAGEMENT IN SUPPORTING THE ADIWIYATA PROGRAM AT MI AL ISHLAH BOBOS CIREBON The Adiwiyata Program is a school initiative aimed at building an environmentally aware and environmentally cultured school community. This study aims to describe the implementation of educational administration management in supporting the Adiwiyata program, including aspects of planning, organizing, implementing, and evaluating. The research method uses a qualitative approach with data collection techniques through interviews, observations, and document analysis. The results show that educational administration management plays an important role in integrating school policies, managing environmental data, preparing work programs, monitoring activities, and involving the school community. Well-organized administration becomes the foundation for the success of the Adiwiyata program, particularly in documentation, environmental-based activity planning, SOP preparation, and school development reports. In conclusion, the success of the Adiwiyata program is strongly influenced by the quality of systematic and sustainable educational administration management. This study also aims to analyze the management of the implementation of the Adiwiyata Program in shaping environmentally caring character at MI Al-Ishlah Bobos. The focus includes planning, organizing, implementing, and evaluating the program, as well as its impact on students’ ecological behavior. The research method used is descriptive qualitative with data collected through interviews, observations, and documentation. The findings indicate that the implementation of the Adiwiyata Program at MI Al-Ishlah Bobos is carried out through structured planning, involvement of the entire school community, and continuous programs such as clean-living habits, waste sorting, greening activities, and the integration of environmental values into learning. The program has proven effective in shaping students’ environmental awareness, although challenges remain, including limited facilities and inconsistent daily behavior among some students.